Perancangan Sistem E-Shop Berbasis E-Commerce untuk Meningkatkan Pemasaran Kerajinan Lokal Naras di Era Digital - Aulia, Selvina; Kurniawan, Asep; Hadai Yani Fitri, Gina (Yayasan Lembaga Studi Makwa, 2023)
This article discusses the challenges faced by Naras local handicrafts in the face of rapid changes in the digital age, especially in marketing, which still relies on traditional methods. The inability to adopt modern technology makes it difficult for Naras local products to compete in an increasingly competitive global market. This research offers an innovative solution by designing an e-commerce e-shop system using the OpenCart platform, specifically designed to support the marketing of local handicraft and garment products to reach a wider audience in an effective and efficient manner. Using a structured research and development (R&D) methodology, this research went through four main stages, namely define, design, develop and disseminate, to create a digital platform that is not only practical in execution, but also strategic in meeting the needs of the digital market. The results show that this OpenCart based e-shop system is valid, practical, and effective in improving the competitiveness of local products and helping artisans overcome geographical limitations that have been an obstacle to the distribution of their products. The platform functions not only as a modern marketing tool, but also as a driver of digital transformation capable of increasing the visibility, attractiveness and contribution of the local creative economy to the global economy. With this innovative approach, Naras' handicraft products have a strong presence in the market.